Management of Retained Genital Piercings: A Case Report and Review - Laura J. Moulton; Amelia M. Jernigan (Case Reports in Obstetrics and Gynecology, 2017)
The prevalence of genital piercing among women is increasing. As the popularity increases, the number of complications from infection, injury, and retained jewelry is likely to rise. Techniques to remove embedded jewelry are not well described in the literature. The purpose of this report was to describe a case of a patient with a retained clitoral glans piercing, discuss a simple technique for outpatient removal, and review current evidence regarding associated risks of clitoral piercings. A 24-year-old female presented to the emergency department with an embedded clitoral glans piercing. Local anesthetic was injected into the periclitoral skin and a small superficial vertical incision was made to remove the ball of the retained barbell safely. In conclusion, among patients with retained genital piercing, outpatient removal of embedded jewelry is feasible. While the practice of female genital piercing is not regulated, piercing of the glans of the clitoris is associated with increased injury to the nerves and blood supply of the clitoris structures leading to future fibrosis and diminished function compared to piercing of the clitoral hood.